Feminist Interpretations of John Rawls - Abbey, Ruth; Abbey, Ruth; Baehr, Amy; Botting, Eileen; Brake, Elizabeth; Chambers, Clare; Hirschmann, Nancy; Laden, Anthony; Richardson, Janice; Schwartzman, Lisa (Re-Reading the Canon, 2021)
In Feminist Interpretations of John Rawls, Ruth Abbey collects eight essays responding to the work of John Rawls from a feminist perspective. An impressive introduction by the editor provides a chronological overview of English-language feminist engagements with Rawls from his Theory of Justice onward. Abbey surveys the range of issues canvassed by feminist readers of Rawls, as well as critics' wide disagreement about the value of Rawls's corpus for feminist purposes. The eight essays that follow testify to the continuing ambivalence among feminist readers of Rawls. From the perspectives of political theory and moral, social, and political philosophy, the contributors address particular aspects of Rawls's work and apply it to a variety of worldly practices relating to gender inequality and the family, to the construction of disability, to justice in everyday relationships, and to human rights on an international level. The overall effect is to give a sense of the broad spectrum of possible feminist critical responses to Rawls, ranging from rejection to adoption.Aside from the editor, the contributors are Amy R. Baehr, Eileen Hunt Botting, Elizabeth Brake, Clare Chambers, Nancy J. Hirschmann, Anthony Simon Laden, Janice Richardson, and Lisa H. Schwartzman